Bacterial Lysis through Interference with Peptidoglycan Synthesis Increases Biofilm Formation by Nontypeable Haemophilus influenzae - Sara Marti (American Society for Microbiology, 2017)
ABSTRACT Nontypeable Haemophilus influenzae (NTHi) is an opportunistic pathogen that mainly causes otitis media in children and community-acquired pneumonia or exacerbations of chronic obstructive pulmonary disease in adults. A large variety of studies suggest that biofilm formation by NTHi may be an important step in the pathogenesis of this bacterium. However, the underlying mechanisms involved in this process are poorly elucidated. In this study, we used a transposon mutant library to identify bacterial genes involved in biofilm formation. The growth and biofilm formation of 4,172 transposon mutants were determined, and the involvement of the identified genes in biofilm formation was validated in in vitro experiments. Here, we present experimental data showing that increased bacterial lysis, through interference with peptidoglycan synthesis, results in elevated levels of extracellular DNA, which increased biofilm formation. Interestingly, similar results were obtained with subinhibitory concentrations of β-lactam antibiotics, known to interfere with peptidoglycan synthesis, but such an effect does not appear with other classes of antibiotics. These results indicate that treatment with β-lactam antibiotics, especially for β-lactam-resistant NTHi isolates, might increase resistance to antibiotics by increasing biofilm formation. IMPORTANCE Most, if not all, bacteria form a biofilm, a multicellular structure that protects them from antimicrobial actions of the host immune system and affords resistance to antibiotics. The latter is especially disturbing with the increase in multiresistant bacterial clones worldwide. Bacterial biofilm formation is a multistep process that starts with surface adhesion, after which attached bacteria divide and give rise to biomass. The actual steps required for Haemophilus influenzae biofilm formation are largely not known. We show that interference with peptidoglycan biosynthesis increases biofilm formation because of the release of bacterial genomic DNA. Subinhibitory concentrations of β-lactam antibiotics, which are often prescribed to treat H. influenzae infections, increase biofilm formation through a similar mechanism. Therefore, when β-lactam antibiotics do not reach their MIC in vivo, they might not only drive selection for β-lactam-resistant clones but also increase biofilm formation and resistance to other antimicrobial compounds.